CELIAC CRISIS: A RARE OR RARELY RECOGNIZED DISEASE - Waheed, Nadia; Cheema, Huma Arshad; Suleman, Hassan; Fayyaz, Zafar; Mushtaq, Iqra; Hashmi, Muhammad Almas (Journal of Ayub Medical College Abbottabad, 2016)
Background: Celiac crisis is a serious life threatening complication of celiac disease characterized by profuse diarrhoea, severe dehydration and metabolic disturbances leading to neuromuscular weakness, cardiac arrhythmias and sudden death. It has been described as rare condition and not well documented in the literature. To improve awareness and facilitate diagnosis of this condition, we studied risk factors, pattern of presentation and management plans of celiac crisis. Methods: It was a descriptive cross sectional study. Patients presenting in emergency room(ER) with profuse diarrhoea leading to severe dehydration, neuromuscular weakness, and metabolic acidosis and electrolyte abnormalities enrolled in the studies after positive serology and small bowel biopsy suggestive of celiac disease. Results: Total 126 patients out of 350 fulfilled the criteria including 54 (42.8%) male and 71 (56.3%) female. The mean age at presentation was 5.25±1.18 years. Risk factors were poor social status (97.60%), consanguinity (96.77%), early weaning with gluten contained diet (93.54%), and Presenting complaints were loose motion (100%), loss of neck holding (96.77%), dehydration (96.77%), polyuria (95.96%), inability to walk (67.74%), abdominal distension (85.86%). Electrolytes imbalances were hypokalaemia (2.4±0.55), hypocalcaemia (7.29±0.66), hypomagnesaemia (1.89±0.50), hypophosphatemia (2.8±0.68), hypoalbuminemia (3.05±0.48) and metabolic acidosis (96%). One hundred & twenty patients were stabilized with GFD and correction of dehydration, acidosis and electrolyte imbalance. Six patients needed parenteral steroids ant total parenteral nutrition (TPN). Recovery time from crisis was mean 5.4±2.73 days (range 3-20 days). Conclusion: Celiac crisis is a common but under recognized problem in developing countries. Commonest presenting feature is neuromuscular paralysis and biochemical abnormality is hypokalaemia. Keywords: Celiac Disease; Celiac crisis; electrolyte abnormality; neuromuscular weakness